Pro-poor pathway towards universal health coverage: lessons from Ethiopia - Kesetebirhan Admasu; Taye Balcha; Tedros Adhanom Ghebreyesus (Edinburgh University Global Health Society, 2016)
Protection from care-related catastrophic expenditures through equitable access to affordable health services is the hallmark of a pro-poor health policy. Over the past two decades, the Government of Ethiopia has implemented policies with a clear intent of reducing poverty and improving the daily lives of its citizens, especially the poor. Guided by these cross cutting pro- poor government policies and spurred by the United Nations Millennium Development Goals (MDGs), the health sector has implemented multi-pronged initiatives towards ensuring every citizen an access to affordable health services without catastrophic expenditures. The health sector initiatives have been guided by evolution of the innovative health programs nationally introduced as well as the needs of the community in each village across the country. Primary focus on the poor and ownership of new health initiatives by the community have been the linchpin for investment at scale.